A new species of Bambuina de Mello, Horta & Bolfarini, 2013 (Orthoptera: Grylloidea: Phalangopsidae: Luzarinae) from the Parque Nacional do Itatiaia, Brazil - Souza-Dias, Pedro G. B.; Borille, Maria V. A.; de Campos, Lucas Denadai (Zootaxa, 2022)
In this study, we describe the second species of the Brazilian genus Bambuina de Mello, Horta & Bolfarini, 2013. Bambuina zikani n. sp. is a cavicolous cricket, found in crevices and natural cavities in the Parque Nacional do Itatiaia, Rio de Janeiro, Brazil. We also highlight the glandular condition of the males’ metanotum and forewings of Bambuina species.